The impacts of the intangible cultural heritage UNESCO policies in France - Fournier, Laurent Sébastien (Traditiones (Ljubljana), 2012)
The article focuses on the "Processional Giants and Dragons in Belgium and France" which were first introduced as a "Masterpiece of the Oral and Intangible Heritage of Humanity" in 2005. This case study documents the implementation of the UNESCO policies in France, analysing the differences between the initial project and its transformations a few years after the nomination. Different French candidatures are examined to understand the impacts of intangible cultural policies in France.
Keywords: ethnology; Etnologija; cultural heritage; Nesnovna kulturna dediščina; Kulturna dediščina; France; UNESCO; Francija